Prevalence and associated factors of depression among adolescent boys and girls in Bangladesh: findings from a nationwide survey. Issue 1 (17th January 2021) - Mridha, Malay Kanti; Hossain, Md Mokbul; Khan, Md Showkat Ali; Hanif, Abu Abdullah Mohammad; Hasan, Mehedi; Mitra, Dipak; Hossaine, Moyazzam; Ullah, Mohammad Aman; Sarker, Samir Kanti; Rahman, S M Mustafizur; Bulbul, Md M Islam; Shamim, Abu Ahmed
Abstract : Objective: To assess the prevalence of and factors associated with depression among adolescent boys and girls. Design: We conducted a nationwide cross-sectional study. Setting: This study was carried out in 82 randomly selected clusters (57 rural, 15 non-slum urban and 10 slums) from eight divisions of Bangladesh. Participants: We interviewed 4907 adolescent boys and 4949 adolescent girls. Primary and secondary outcome measures: The primary outcome measure was 'any depression' and the secondary outcome measures were types of depression: no or minimal, mild, moderate, moderately severe and severe. Results: The overall prevalence of no or minimal, mild, moderate, moderately severe and severe depression was 75.5%, 17.9%, 5, 4%, 1.1% and 0.1%, respectively. Across most of the sociodemographic, lifestyle and anthropometric strata, the prevalence of any depression was higher among adolescent girls. In both sexes, depression was associated with higher age, higher maternal education, paternal occupation e.g., business, absence of a 6–9-year-old member in the household, food insecurity, household consumption of unfortified oil, household use of non-iodised salt, insufficient physical activity (adjusted odds ratio, AOR: 1.24 for boys, 1.44 for girls) and increased television viewing time e.g., ≥121 minute/day (AOR: 1.95 for boys, 1.99 for girls). Only among boys, depression was also associated with higher paternal education e.g., complete secondary and above (AOR: 1.42), absence of another adolescent member in the household (AOR: 1.34), household use of solid biomass fuel (AOR: 1.39), use of any tobacco products (AOR: 2.17), and consumption of processed food (AOR: 1.24). Only among girls, non-slum urban residence, Muslim religion, and household size ≤4 were also associated with depression. Conclusion: The prevalence of depression among adolescent boys and girls is high in Bangladesh. In most sociodemographic, lifestyle and anthropometric strata, the prevalence is higher among girls. In this age group, depression is associated with a number of sociodemographic and lyfestyle factors. The government of Bangladesh should consider these findings while integrating adolescent mental health in the existing and future programmes.